South Africa : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2020)
This Selected Issues paper studies the growth-inflation trade-off of monetary policy in South Africa. The combination of low growth and stubbornly high inflation expectations for a protracted period has complicated monetary policy decisions. The IMF staff analysis contributes to the ongoing growth-inflation trade-off discussion in South Africa, concluding that there is limited growth trade-off of monetary policy efforts to anchor inflation expectations at a lower level at present. The findings in this note suggest that the South African Reserve Bank should continue its efforts of anchoring inflation and inflation expectations at a lower level because monetary policy lends limited support to growth dampened by structural issues. During the 2010s, domestic demand growth responded little to monetary policy action. The environment of weak growth, low interest rates, and relatively moderate inflation (expectations) could have muted monetary policy transmission. Ultimately, the constraints to economic growth need to be removed. Meanwhile, inflation expectations continue to respond to monetary policy action albeit to a lesser extent. Monetary policy transmission through demand has weakened--demand growth does not systematically respond to monetary policy action nor does core inflation--but the exchange rate and credibility channels appear to remain operational.